Persuasive Interactional Strategies In The Abdullah Al-Mudaifer-Mohammed Bin Salman Interview On Saudi Arabia’s Vision 2030: Ecolinguistics Study - Alaufi, Hamed Marzuq; Obeng, Samuel Gyasi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Studies on political interviews abound in the linguistics, sociology, psychology, literary studies, cognitive science, and critical discourse analysis literature. Working within the framework of Critical Discourse Analysis, this study identified and discussed discursive strategies employed by Abdullah Al-Mudaifer and Mohammed Bin Salman (MBS) in an interview on Saudi’s Vision 2030. The identified discursive strategy used by MBS indexed power, control, and ideology and included stroking and political pronouns, indexing agency, closeness, and group identity. Others were positive self-representation, the number game, address and reference, antithetic constructions, relational processes, admitting errors and promising change, and questioning the interviewer’s questions. Abdullah Al-Mudaifer produced texts of resistance and enacted status asymmetry. The interview participants’ communicational goals and ideologies were relevant in managing delicate speech acts.